Deconstructing the Value-Neutrality of Technology: - Christian Gardoni (Journal of Digital Media & Interaction)
It is often argued that technology is neutral. Even in the academic world there is still debate today whether it incorporates intrinsic moral values ​​or whether, instead, it all depends on the use that is made of it. In this article this concept will be examined starting from the classification made by Luciano Floridi, in an attempt to dispel this mirage. It will be also discussed why and how Media Education should consider this assumption and include it in its repertoire as a first principle that guides every other reflection and transmittable skill in favor of a conscientization and literacy which it aims to achieve.